The guidance hierarchy to describe heart in Holly Quran,(Ungrateful hearts): The guidance hierarchy to describe heart in Holly Quran,(Ungrateful hearts) (Journal of the College of Education for Women, 2019)
Abstract:In the name of God , most Gracious , most mercifulThe Holy Quran conciders the celestial book which consultslanguages with its accents , and consults the people with their circumstancesand it takes care of all worships.We find that Holy Quran consults atheist human and afaithless one ,therefore , it aspect the orabion of God to human “s heart as a results , it isone of an incapacitation of Holly Quran in This research.WE try to taik about special vocables which relate to hearts ofunfaithful hummance , so we mentio these vocables in a guidance hierarchytable in the end of this research.